Implementasi Nilai Tabligh Pada Tenaga Pengajar Dalam Proses Belajar Mengajar di Madrasah Aliyah Negeri Mojokerto - Iffa Amalia; Sri Herianingrum (Universitas Airlangga, 2015)
Islam teaches every human being which have been blessed by Allah SWT with various advantages to be thankful for what they have by utilizing his/her ability through dig and developing his/her potential in a good way, so that it can be meaningful for him/herself as well as to other people. The teachers at school, which has been trusted by other parties to constantly, transfers his/her knowledge and conduct their pupil according to the characteristics of Rasulullah SAW so that they’re able to reach success in that school, and of the characteristic is tabligh. The outcome of this research is, teachers have implemented tabligh on the teaching –learning process communicatively, it was proofed by the fulfillment of 5 indicators which are; communication, model, education, wisdom and firmness which caused the escalation of student’s morality until today. The teachers which have implemented tabligh are able to create a pleasant and conducive class with Islamic ethics. The implementation of tabligh is able to create excellent and high quality human resources.The excellent and high quality human resources will be able to build his/her economiccondition as well as build the nation’s.